Traffic accidents and their relationship with serum levels of ethanol evaluated in the La Libertad región, 2014 - Rodríguez Vega, Juan Luis (2016)
The present investigation was a cross - sectional and retrospective study, with the objective of relating ethanol serum levels to the types of traffic accidents that occurred in the Libertad region during 2014, where 981 samples of blood corresponding to equals Number of individuals. It was found that the type of accident with the highest percentage is 78.28% was the shock, and the lowest percentage is 4.20% of abuse. It is also observed that the highest percentage of these drivers (72.47%), its concentration is 0.5 to 1.5 g / l, where it is included drunken state, where the possibility of traffic accidents caused by drivers is greatly increased, Due to the diminution of the reflexes and difficulty in the visual adaptation and especially in the dark. Then follows the drivers in absolute drunken state (16.53%) whose concentration in blood 1.5 to 2.5 g / l. The drivers have a lot of aggressiveness, and difficulty in perceiving color, shape, movements and dimensions. Finally, the percentages of drivers in the subclinical state (11.00%), whose alcohol concentration is 0.1 to 0.5 g / l in the blood, has the possibility of an accident because drivers have a false estimate of speed and distance.